Diagnosis of Idiopathic GHD in Children Based on Response to rhGH Treatment: The Importance of GH Provocative Tests and IGF-1 - Felício, João Soares; Janaú, Luísa Corrêa; Moraes, Marcelle Alves; Zahalan, Nathalie Abdallah; de Souza Resende, Fabrício; de Lemos, Manuela Nascimento; de Souza Neto, Norberto Jorge Kzan; Farias de Franco, Isabela Imbelloni; Leitão, Loyane Tamyres Costa; Silva, Lilian de Souza d'Albuquerque; de Oliveira, Maria Clara Neres Iunes; de Alcântara, Angélica Leite; et al. (Frontiers in Endocrinology, 2019)
Purpose: Serum IGF-1 (Insulin like growth factor 1) and Growth Hormone (GH) provocative tests are reasonable tools for screening and diagnosis of idiopathic GH Deficiency (IGHD). However, the average cut-off points applied on these tests have a lower level of evidence and produce large amounts of false results. The aim of this study is to evaluate the sensitivity, specificity, and accuracy of IGF-1 and GH stimulation tests as diagnostic tools for IGHD, using clinical response to recombinant human GH (rhGH) treatment as diagnostic standard [increase of at least 0.3 in height standard deviation (H-SD) in 1 year]. Methods: We performed a prospective study with 115 children and adolescents presenting short stature (SS), without secondary SS etiologies such as organic lesions, genetic syndromes, thyroid disorders. They were separated into Group 1 [patients with familial SS or constitutional delay of growth and puberty (CDGP), not treated with rhGH], Group 2 (patients with suspicion of IGHD with clinical response to rhGH treatment), and Group 3 (patients with suspicion of IGHD without growth response to rhGH treatment). Then, they were assessed for diagnostic performance of IGF-1, Insulin Tolerance Test (ITT) and clonidine test (CT) alone and combined at different cut-off points. Results: Based on the ROC curve, the best cut-off points found for IGF-1, ITT, and CT when they were used isolated were −0.492 SDS (sensitivity: 50%; specificity: 53.8%; accuracy: 46.5%), 4.515 μg/L (sensitivity: 75.5%; specificity: 45.5%; accuracy: 52.7%), and 4.095 μg/L (sensitivity: 54.5%; specificity: 52.6%; accuracy: 56.9%), respectively. When we had combined IGF-1 with−2SD as cut-off alongside ITT or CT, we found 7 μg/L as the best cut-off point. In this situation, ITT had sensitivity, specificity and accuracy of 93.9, 81.8, and 90.1%, while CT had 93.2, 68.4, and 85.7%, respectively. Conclusion: Our data suggest that diagnosis of IGHD should be established based on a combination of clinical expertise, auxologic, radiologic, and laboratorial data, using IGF-1 at the −2SD threshold combined, with ITT or CT at the cut-off point of 7 μg/L. Additional studies, similar to ours, are imperative to establish cut-off points based on therapeutic response to rhGH in IGHD, which would be directly related to a better treatment outcome.